Linking psychology and sustainability: research gaps and future directions - Mohd Mahudin, Nor Diana (The Pacific Rim Education for Sustainable Development Alliance (PRESDA) Foundation, Japan, 2014)
Although there is a growing literature concerning sustainability that is grounded in psychology, particularly environmental psychology, much of the current knowledge in this field is still derived from the works of researchers in ecology, environmental science, geography, architecture, and sociology. This renders psychology of sustainability as an increasingly important research area, but one in need of more evidence-based studies with stronger links between theories, methods, and practice. To address this concern, a brief overview of issues, developments, and emerging areas of research for sustainability where psychologists can contribute, is presented. Six distinct, but interdependent research ideas that may provide future direction in this field are identified. These include (1) demand for an in-depth examination of environmental values, (2) improvement in the measurement of sustainability indicators, (3) better understanding of the relationships between sustainability and cultures, (4) better integration of theories and applied research drawn from other disciplines, (5) establishment of innovative strategies for public engagement and dissemination of research findings, and (6) and more intervention research. Drawing from these results, some implications that would provide ideas for future work are presented.